Food Insecurity and Substance Use in HIV-Infected Adults in the Miami Adult Studies on HIV (MASH) Cohort (P04-066-19). (13th June 2019) - Martinez, Sabrina; Campa, Adriana; Zarini, Gustavo; Liu, Qingyun; Seminario, Leslie; Jasmin, Juphshy; Hernandez, Jacqueline; Teeman, Colby; Baum, Marianna; Tamargo, Javier
Abstract: Objectives: It has been estimated that about half of people living with HIV (PLWH) in inner-cities may experience food insecurity. Substance use is common among PLWH and a risk factor for food insecurity. The objective of this study was to evaluate the relationship between substance use and food security in HIV + adults in the MASH cohort in Miami, Florida. Methods: A cross-sectional analysis of data from an observational longitudinal study was conducted in 324 HIV + adults on antiretroviral therapy. After obtaining informed consent, validated questionnaires on demographics, socioeconomic status and illicit drug use and the Alcohol Use Disorders Identification Test (AUDIT) were collected. Polysubstance use was defined as >1 substance, including drugs and alcohol. Food insecurity was determined using the US Household Food Security Survey. HIV disease progression parameters, CD4 cell count and HIV viral load, were obtained from medical records with the participants' permission. Wilcoxon, chi-square and regression analyses were completed, adjusted for age, gender, race/ethnicity, income, education, household size and quality of life. Results: The median age was 53.61 (IQR = 49.4–58.3) years, 59.6% were male, 66.4% were African American, and 70% had an annual income of $15, 000 a year or less. Most, 84% used at least one illicit drug, 55.9% were polysubstance users and 25.6% were food insecure. Food insecurity was higher in those who used marijuana ( P  = 0.007) and polysubstance use ( P  < 0.001) compared with non-users. Cocaine users had higher food insecurity compared with non-users which trended towards significance ( P  = 0.076). In a regression model, opiate users were at significantly higher risk for food insecurity than non-users (OR = 1.99, 95% CI: 1.037, 3.80, P  = 0.039). Polysubstance users had 3 times greater risk of experiencing food insecurity compared with non-users (OR = 3.22, 95% CI: 1.70, 6.13, P  < 0.001). Food insecurity was also associated with having a detectable HIV viral load ( P  = 0.034). Conclusions: The current study shows that food insecurity is associated with substance use, alone or in combination, and with uncontrolled HIV viral load among PLWH living in poverty. In resource poor settings, substance use treatment and nutritional services are greatly needed in order to advance HIV treatment and care. Funding Sources: National Institute on Drug Abuse 5U01DA040381–03.